Passive vibration suppression using inerters for a multi-storey building structure. (September 2016) - Zhang, Sara Ying; Jiang, Jason Zheng; Neild, Simon
Abstract: This paper investigates the use of inerters for vibration suppression of a multistorey building structure. The inerter was proposed as a two-terminal replacement for the mass element, with the property that the applied force is proportional to the relative acceleration across its terminals. It completes the force-current mechanical-electrical network analogy, providing the mechanical equivalent to a capacitor. Thus allows all passive mechanical impedances to be synthesised. The inerter has been used in Formula 1 racing cars and applications to various systems such as vehicle suspension have been identified. Several devices that incoporate inerter(s), as well as spring(s) and damper(s), have also been identified for vibration suppression of building structures. These include the tuned inerter damper (TID) and the tuned viscous mass damper (TVMD). In this paper, a three-storey building model with an absorber located at the bottom subjected to base excitation is studied. Four simple absorber layouts, in terms of how spring, damper and inerter components should be arranged, have been studied. In order to minimise the maximum relative displacement of the building, the optimum parameter values for each of the layouts have been obtained with respect to the inerter's size.